2019
DOI: 10.1016/s0140-6736(19)32519-x
|View full text |Cite|
|
Sign up to set email alerts
|

Application of non-HDL cholesterol for population-based cardiovascular risk stratification: results from the Multinational Cardiovascular Risk Consortium

Abstract: Background The relevance of blood lipid concentrations to long-term incidence of cardiovascular disease and the relevance of lipid-lowering therapy for cardiovascular disease outcomes is unclear. We investigated the cardiovascular disease risk associated with the full spectrum of bloodstream non-HDL cholesterol concentrations. We also created an easy-to-use tool to estimate the long-term probabilities for a cardiovascular disease event associated with non-HDL cholesterol and modelled its risk reduction by lipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
163
0
15

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 213 publications
(193 citation statements)
references
References 40 publications
15
163
0
15
Order By: Relevance
“…Here, we showed that the lowest hazard for CVD was found in women and men with the lowest non-HDL-C concentrations. This is in accordance with outcomes revealed from the Multinational Cardiovascular Risk Consortium, where a continuous and linear increase for higher non-HDL-C concentrations was observed [15]. Additionally, several works suggest that the non-HDL-C/HDL-C ratio is superior to traditional lipid markers in estimating arterial stiffness and atherosclerosis, with this association being more evident in the case of women [24,25].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Here, we showed that the lowest hazard for CVD was found in women and men with the lowest non-HDL-C concentrations. This is in accordance with outcomes revealed from the Multinational Cardiovascular Risk Consortium, where a continuous and linear increase for higher non-HDL-C concentrations was observed [15]. Additionally, several works suggest that the non-HDL-C/HDL-C ratio is superior to traditional lipid markers in estimating arterial stiffness and atherosclerosis, with this association being more evident in the case of women [24,25].…”
Section: Discussionsupporting
confidence: 87%
“…Nevertheless, no robust conclusions exist, while their clinical use is often overlooked [4]. On the other hand, the hitherto literature related with these alternative lipid biomarkers lacks in the aforementioned need for a sex-specific orientation [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The inclusion of apolipoprotein-B-related measures leads to modest incremental increases in predictive performance [20]. Pooled data from over 500,000 individuals across 44 cohorts identified non-highdensity lipoprotein (non-HDL) cholesterol (an approximation to the number of apolipoprotein-B-containing particles) to strongly associate with risk of incident cardiovascular disease [21]. When the concentrations of apolipoprotein B and LDL cholesterol are discordant in individuals, apolipoprotein B has a stronger association with risk of cardiovascular disease (CVD) than LDL cholesterol [22].…”
Section: Introductionmentioning
confidence: 99%
“…Altered lipid metabolism, which is relevant to hematopoietic activity and the risk of several immunological diseases, including cardiovascular disease, obesity and cancer, has recently received increasing attention [72,73]. Fatty acids provide an efficient way to generate energy via fatty acid oxidation (FAO, also known as β-oxidation), through which acetyl-CoA is produced to participate in the tricarboxylic acid (TCA) cycle, oxidative phosphorylation (OXPHOS) and fatty acid synthesis to meet the substantial cellular energy needs in the TME [74,75].…”
Section: Lipid Metabolismmentioning
confidence: 99%